2014
DOI: 10.1002/14651858.cd007366.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for treating painful nipples among breastfeeding women

Abstract: There was insufficient evidence that glycerine gel dressings, breast shells with lanolin, lanolin alone, or the all-purpose nipple ointment significantly improved maternal perceptions of nipple pain. The results from these four trials of good methodological quality suggested that applying nothing or just expressed breast milk may be equally or more beneficial in the short-term experience of nipple pain than the application of an ointment such as lanolin.The quality of the evidence for this review did not lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 60 publications
1
72
0
15
Order By: Relevance
“…It is important to emphasize that the correct accomplishment of the RN handgrip in the breast implies a reduction of crack processes in the nozzles (8) . The fact that the present research does not show statistically significant differences regarding the nozzles (worsening in their condition, as reported in the literature (8,11) ) could be attributed to the speech-language intervention with breastfeeding, in the first hours of life, a period in which these problems can be more easily prevented. (42) 3 (9) 24 (18) 1 (3) 16 (12) M-H = Mantel-Haenszel Test (p<0.05); LTR = Likelihood Ratio Test for the longitudinal logistic model (p<0.05) Subtitle: <24h = Group 1-Group formed by newborn-born dyads (NBs), whose newborn was less than 24 hours postnatal at the time of initial observation; > 24h = G2 -Group formed by dyads mothers-NBs, whose NB was postnatal age greater than or equal to 24 hours, at the time of the initial observation; Dependent = Post Natal age (24h) X Moments (baseline, speech therapy or follow-up) Subtitle: <24h = Group 1-Group formed by newborn-born dyads (NBs), whose newborn was less than 24 hours postnatal at the time of initial observation; > 24h = G2 -Group formed by dyads mothers-NBs, whose NB was postnatal age greater than or equal to 24 hours, at the time of the initial observation; Dependent = Post Natal age (24h) X Moments (baseline, speech therapy or follow-up)…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…It is important to emphasize that the correct accomplishment of the RN handgrip in the breast implies a reduction of crack processes in the nozzles (8) . The fact that the present research does not show statistically significant differences regarding the nozzles (worsening in their condition, as reported in the literature (8,11) ) could be attributed to the speech-language intervention with breastfeeding, in the first hours of life, a period in which these problems can be more easily prevented. (42) 3 (9) 24 (18) 1 (3) 16 (12) M-H = Mantel-Haenszel Test (p<0.05); LTR = Likelihood Ratio Test for the longitudinal logistic model (p<0.05) Subtitle: <24h = Group 1-Group formed by newborn-born dyads (NBs), whose newborn was less than 24 hours postnatal at the time of initial observation; > 24h = G2 -Group formed by dyads mothers-NBs, whose NB was postnatal age greater than or equal to 24 hours, at the time of the initial observation; Dependent = Post Natal age (24h) X Moments (baseline, speech therapy or follow-up) Subtitle: <24h = Group 1-Group formed by newborn-born dyads (NBs), whose newborn was less than 24 hours postnatal at the time of initial observation; > 24h = G2 -Group formed by dyads mothers-NBs, whose NB was postnatal age greater than or equal to 24 hours, at the time of the initial observation; Dependent = Post Natal age (24h) X Moments (baseline, speech therapy or follow-up)…”
Section: Discussionsupporting
confidence: 62%
“…The literature (11,23,24) reported that the anatomical and physiological conditions of breasts and beaks may influence the effectiveness of breastfeeding, since nipple trauma, regorgement, incomplete emptying of the breasts and cracks cause pain and discomfort, interfering with well-being and sensation of pleasure of the nurse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Снижение травматизации соска позволяет сущест-венно минимизировать риски его инфицирования во время лактации, предотвращает развитие лактостазов и, как следствие, отказ от грудного вскармливания [16][17][18][19]. Про лон гирование периода лактации в настоящее вре-мя рассматривается не только как профилактическая мера для снижения случаев онкологических заболева-ний у женщин в последующем (рак молочной железы, доброкачественные новообразования молочной желе-зы), но и как фактор существенного влияния на здоровье и дальнейшее развитие ребенка [20][21][22].…”
Section: обсуждение результатовunclassified